Urgensi Zakat Dan Waqaf Dalam Pembangunan Ekonomi Syariah Kontemporer - Fadilah, Nurul; Zen, Muhamad (Abdurrauf Law and Sharia, 2024)
Abstract:. Zakat and waqf are two significant instruments in economic development. The purpose of this research is to describe zakat and waqf in the perspective of Islamic economics; its urgency; opportunities and innovations in the digital era as well as challenges and solutions. This research method uses descriptive qualitative method with library research data source. The results show that zakat and waqf are two important instruments in contemporary Islamic economics that not only function as an obligation of Muslims but also as a means to achieve social welfare and sustainable economic development. The essence of zakat waqf is economic empowerment; economic and social improvement; and human resource development. The opportunities and innovations of zakat in the digital era, by utilizing digital technology and good governance principles, are essential to increase effectiveness and transparency. This will encourage public participation and strengthen trust in zakat management institutions. Meanwhile, opportunities and innovations for waqf with digital platforms for raising waqf; cash waqf and investment in smart contracts and blockchain; cash waqf and investment; education and awareness through social media; mobile applications for donations; data analyst; digital waqf for startups. In addition, there are some challenges such as lack of public awareness of zakat and waqf; the concept of zakat and waqf is often misunderstood; changes in economic dynamics. While the solution is education and socialization Keywords: Zakat; Waqf; Sharia Economics Abstrak: Zakat dan wakaf merupakan dua instrumen yang signifikan dalam pembangunan  ekonomi. Tujuan dari penelitian ini adalah mendeskripsikan zakat dan wakaf dalam pespektif ekonomi syariah; urgensinya; peluang dan inovasi di era digital serta tantangan dan solusinya. Metode penelitian ini menggunakan metode deskriptif kualitatif dengan sumber data library research. Hasil Penelitian menunjukkan bahwa zakat dan wakaf merupakan dua instrumen yang penting dalam ekonomi syariah kontemporer yang tidak hanya berfungsi sebagai kewajiban umat muslim semata melainkan sebagai sarana untuk mencapai kesejahteraan sosial dan pembangunan ekonomi yang berkelanjutan. Ugensi zakat wakaf adalah pemberdayaan ekonomi; peningkatan ekonomi dan sosial; serta pengembangan sumber daya manusia. Peluang dan inovasi zakat diera digital, dengan memanfaatkan teknologi digital dan prinsip tata kelola yang baik, sangat penting untuk meningkatkan efektivitas dan transparansi. Hal ini akan mendorong partisipasi masyarakat dan memperkuat kepercayaan terhadap lembaga pengelola zakat. Sedangkan peluang dan inovasi terhadap wakaf dengan platform digital untuk penggalangan wakaf; wakaf uang dan investasi smart contracts dan blockchain; wakaf uang dan investasi; edukasi dan kesadaran melalui media sosial; aplikasi mobile untuk donasi; data analytist; wakaf digital untuk starup. Selain itu Adapun beberapa tantangannya kurangnya kesadaran Masyarakat terhadap zakat dan wakaf; konsep zakat dan wakaf seingkali disalah pahami; perubahan dinamika ekonomi. Sedangkan solusinya yaitu edukasi dan sosialisasi; peningkatan manajemen; inovasi model wakaf dan zakat; regulasi yang mendukung; transparan dan akuntabilitas.